Solar fresh heat-lock container / Nurhazimah Nordin ... [et al.] - Nordin, Nurhazimah; Mohd Nazir, Nur Sulaiman; Azmi, Mohamad Fakhruddin; Shahrul Layali, Arissa Elfeera; Selasa, Nur Izzati; Rahim, Nurul Izzati (2024)
Description of the business and product concepts: The Solar Fresh Heat-Lock Container introduces a groundbreaking concept to the lunchbox market by utilizing solar energy to reheat food, coupled with an intelligent gas detector (MQ-135) for detecting stale food. This innovative lunchbox, a collaboration between Mr.DIY and Buffalo brands, aims to revolutionize on-the-go dining by addressing the common challenge of keeping meals warm while outside the home. Its features distinguish it as an advanced, tech-driven solution in the market, elevating the traditional lunchbox to new heights of convenience and sustainability. The target market and projections Targeting a diverse audience, including students and office workers, the Solar Fresh Heat-Lock Container anticipates strong market resonance. Initial projections, particularly the 51.5% user interest in the reheating function based on survey data, indicate a promising market reception. The lunchbox aligns with the lifestyle needs of individuals seeking portable and efficient solutions for warm meals, positioning itself as a versatile and essential accessory for those on the move.